Support group system and psycho-social well-being of people living with HIV in selected anti-retroviral clinics in Oyo State, Nigeria (2022)
This study examined the effect of support group System on the psycho-social well-being of PLHW in selected anti- retroviral clinics in Oyo state. The study adopted the survey design. A total number of 321 PLWH attending six selected ART clinics in Oyo State, Nigeria and actively participating support group meetings consistently for the past three months prior to the study were purposively selected for the study. Support Group System on Psycho-social Well- being Questionnaire (r=0.) was used for data collection. Four (4) hypotheses were tested at p<05. Data collected were analyzed at univariate and bivariate levels using SPSS Version 25. The study established that female respondents (x = 61.76) living with HIV has the better level of group support compared to male (x = 56.78) (Crit-t = 1.96, Cal.t = 2.216, DF = 319, p(0.027)<0.05 level of significance). For psychosocial well-being of PLWHA, the result shows that there was a significant relationship between group support and emotional wellbeing (r=.409), physical wellbeing (r=.266), and social wellbeing (r=.263), respectively. Based on the findings, it is recommended that that group support is necessary for the psychosocial well-being of PLWHA, through the provision of efficient and functional support groups in all ART clinics for people living with HIV/AIDS. There should also be adequate social Services and relevant health policies to better the lives of PWHA.